2016
DOI: 10.1097/md.0000000000004446
|View full text |Cite
|
Sign up to set email alerts
|

A mobile application improves therapy-adherence rates in elderly patients undergoing rehabilitation

Abstract: Medication adherence is crucial for success in the management of patients with chronic conditions. This study analyzes whether a mobile application on a tablet aimed at supporting drug intake and vital sign parameter documentation affects adherence in elderly patients.Patients with coronary heart disease and no prior knowledge of tablet computers were recruited. They received a personal introduction to the mobile application Medication Plan, installed on an Apple iPad. The study was conducted using a crossover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 33 publications
1
81
0
7
Order By: Relevance
“…We considered 83 of these to be eligible and retrieved the full-text articles. Of these, nine studies reported outcome data eligible for meta-analysis 12 13 15 16 22–26. The screening process and reasons for exclusion are reported in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We considered 83 of these to be eligible and retrieved the full-text articles. Of these, nine studies reported outcome data eligible for meta-analysis 12 13 15 16 22–26. The screening process and reasons for exclusion are reported in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of participants in the intervention group was reported by eight studies and ranged from 20.3 (SD 4.0)22 to 73.8 (SD 8)12; the mean of the mean ages across these eight studies was 56.7 years. One study did not report the mean age but presented the percentage of participants whose age fell within a series of bandwidths 15.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2016 randomized controlled crossover study of a mobile app focused on supporting drug intake and vital sign documentation, researchers found that patients who used the iPad app showed greater adherence for both medication intake and blood pressure measurement than a paper-based control group [58]. Another randomized controlled study published in 2016 found that overweight and obese adults who used a social support app lost on average 3 kg more than patients using a self-monitoring control app over the course of the study [59].…”
Section: Discussionmentioning
confidence: 99%